Petrophysical characteristics of upper cretaceous rocks of Al-Querdaha sheet (Latakia University Journal -Basic Sciences Series, 2018)
An evaluation of the limestone rocks in Al-Querdaha sheet, Aljawbeh section, as building materials was done in this research 10 stations along 4 km from the selected section. The research included a theoretical study and field, experimental and analytical laboratory works. and office works.Tests were carried out on samples to determine physical and mechanical properties and thus to determine their validity for various construction purposes.Petrophysical tests showed that studied models of first marl of Slenfeh, first marl of Bab Abdullah, first wall of Bab Abdullah, second wall of Bab Abdullah and Santonian-Coniacian are good for construction works according to Syrian and American standards catalogues (Suitable for floors and drawers covering, for internal and external wall covering and for decoration works), because they have high density, low water absorption, low porosity and high resistance according to Syrian and American Standard Specifications. The Rocks of second marl of Slenfeh, second marl of Bab Abdullah and Turonian are of medium importance. Rocks of first and second walls of Slenfeh are of low density and high water absorption, preferably used in low-grade concrete in roads and pavements.Samples of first marl of Bab- Abdullah are acceptable to use as marble rocks, according to Syrian and American Standard Specifications.Samples of first marl of Slenfeh, first marl of Bab- Abdullah, first and second walls of Bab- Abdullah, and Santonian-Coniacian are good to be used as gravel for good beton according to Abrasion and Corrosion Tests, while rocks of first wall of Slenfeh, second marl of Slenfeh, second wall of Slenfeh, are good for normal beton.